Overview of KAGRA: KAGRA science. (12th August 2020) - Akutsu, T; Ando, M; Arai, K; Arai, Y; Araki, S; Araya, A; Aritomi, N; Asada, H; Aso, Y; Bae, S; Bae, Y; Baiotti, L; et al.
Abstract: KAGRA is a newly build gravitational wave observatory, a laser interferometer with 3 km arm length, located in Kamioka, Gifu, Japan. In this paper, one of a series of articles featuring KAGRA, we discuss the science targets of KAGRA projects, considering not only the baseline KAGRA (current design) but also its future upgrade candidates (KAGRA+) for the near to middle term ( 5 years).